Pressure assisted enhancement in superconducting properties of Fe substituted NbSe2 single crystal - Manikandan Krishnan (Nature Portfolio, 2018)
Abstract The impact of hydrostatic pressure (P) up to 1 GPa on T c , J c and the nature of the pinning mechanism in FexNbSe2 single crystals have been investigated within the framework of the collective theory. We found that the pressure can induce a transition from the regime where pinning is controlled by spatial variation in the critical transition temperature (δT c ) to the regime controlled by spatial variation in the mean free path (δℓ). Furthermore, T c and low field J c are slightly induced, although the J c drops more rapidly at high fields than at ambient P. The pressure effect enhances the anisotropy and reduces the coherence length, resulting in weak interaction of the vortex cores with the pinning centers. Moreover, the P can induce the density of states, which, in turn, leads to enhance in T c with increasing P. P enhances the T c with the rates of dT c /dP of 0.86, 1.35 and 1.47 K/GPa for FexNbSe2, respectively. The magnetization data are used to establish a vortex phase diagram. The nature of the vortices has been determined from the scaling behaviour of the pinning force density extracted from the J c –H isotherms and demonstrates the point pinning mechanism.